The Combined Treatment of Chinese Herbal Medicines Is Correlated with a Lower Risk of Rheumatoid Arthritis in Patients with Depression: Evidence from a Population-Based Patient–Control Study - Chieh-Tsung Yen; Hanoch Livneh; Hui-Ju Huang; Ming-Chi Lu; Wei-Jen Chen; Tzung-Yi Tsai (Pharmaceuticals)
Background: Major depression places psychological strain on the individual that may increase the risk of developing rheumatoid arthritis (RA). Though the use of Chinese herbal medicines (CHMs) is widespread in clinical practice, its effect on the prevention of RA incidents is still unknown. This study aimed to evaluate the association between CHMs use by patients with depression and their subsequent risk of being diagnosed with RA. Methods: This nested case–control study used claims data from a nationwide insurance database. We identified patients aged 20–70 years with newly diagnosed depression and without pre-existing RA between 2002 and 2010. We enrolled those with RA onset occurring after depression by the end of 2013 (n = 973). Randomly matched controls were selected from the remaining patients with depression but without RA (n = 1946). Conditional logistic regression analysis was executed to assess the association between CHMs use and RA onset. Data are presented as p-values with the significance set at 0.05 and as odds ratios (ORs) with 95% confidence intervals (CIs). Results: In this study, we found that adding CHMs treatment to conventional antidepressants greatly decreased the subsequent risk of RA among patients with depression, with an ORs of 0.64 (95% CIs: 0.57–0.76). Those using CHMs for more than three years had the most striking benefit, with a 61% lower risk of RA. Notably, initiating CHMs within the first 2 years after depression onset resulted in the greatest decrease in the RA risk. Conclusion: Using CHMs with conventional antidepressant therapy reduced the RA risk among patients with depression. Further well-designed randomized controlled trials are needed to determine the molecular mechanism underlying the action of these herbal agents.